The Cleveland Street Railway Settlement - Bemis, Edward W. (Quarterly Journal of Economics, 1910)
The Cleveland Street Railway Settlement Get access Edward W. Bemis Edward W. Bemis Department of Water Supply, New York Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 24, Issue 3, May 1910, Pages 550–560, https://doi.org/10.2307/1885211 Published: 01 May 1910